Enhancing Speaking Ability through Short Movie - Paramitasari, Ayu (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2021)
Speaking is one difficult element in English Language Education. It is complex and need some practice for developing this skill. Speaking also uses for communication. When we speak we produce the text and it should be meaningful. In the nature of communication, we can find the speaker, the listener, the message and the feedback. Speaking could not be separated from pronunciation as it encourages learners to learn the English sounds. One of the techniques is movie. Movie is interesting media for student to learn English language and developing their speaking ability. Movie can be effective media for teaching activity in the class, because movie is one of interactive media which can be used for teaching student understanding and comprehension of their ability besides that watching films or movies is a fun way to improve our English especially speaking ability. the benefits of using film in the language learning classroom, it is not surprising that many teachers are keen to use film with their students,and an increasing number of them are successfully integrating film into the language-learning syllabus.